Relationship between gut microbiota dysbiosis and immune indicator in children with sepsis - Xia Lin; Mohnad Abdalla; Junjie Yang; Lei Liu; Yali Fu; Yanli Zhang; Shuchun Yang; Han Yu; Yongsheng Ge; Sufang Zhang; Guiyun Kang; Wei Dang; et al. (BMC, 2023)
Abstract Sepsis is a life-threatening multiple-organ injury caused by disordered host immune response to microbial infection. However, the correlation between gut microbiota dysbiosis and immune indicators remains unexplored. To address this gap in knowledge, we carried out 16 S rDNA sequencing, analyzed clinical fecal samples from children with sepsis (n = 30) and control children (n = 25), and obtained immune indicators, including T cell subtypes (CD3+, CD3+CD4+, CD3+CD8+, and CD4/CD8), NK cells, cytokines (IL-2, IL-4, IL-6, IL-10, TNF-α and IFN-γ), and immunoglobulin indices (IgA, IgE, IgM and IgG). In addition, we analyzed the correlation between gut microbiota dysbiosis and immune indicators, and evaluated the clinical discriminatory power of discovered bacterial biomarkers. We found that children with sepsis exhibited gut bacterial dysbiosis and low alpha diversity. The Spearman's rank correlation coefficient suggested that Rhodococcus erythropolis had a significantly positive correlation with IFN-γ and CD3 + T cells. Klebsiella pneumoniae and Streptococcus mitis were significantly correlated with NK cells. Bacteroides uniformis was significantly positively correlated with IgM and erythrocyte sedimentation rate, and Eubacterium eligens was significantly positively correlated with IL-4 and CD3+CD8+ T cells. The biomarkers discovered in this study had strong discriminatory power. These changes in the gut microbiome may be closely related to immunologic dysfunction and to the development or exacerbation of sepsis. However, a large sample size is required for verification.